KAJIAN HUBUNGAN ANTARA PELAYANAN KESEHATAN IBU DAN ANAK DENGAN ANGKA KEMATIAN NEONATAL DI KOTA MEDAN - EKA SAMUEL PARULIAN HUTASOIT (LP2MTBM MAKARIOZ, 2021)
Medan City experienced 410 cases of childbirth during 2021, while the number of deaths was 210 cases. This happens because there is still no awareness from pregnant women to always increase nutritious food and have no impact on the process of pregnancy. In addition, less socialization from the Medan City Health office in preventing an increase in maternal and infant deaths, especially neonatal deaths that occur in infants, so that this socialization process will affect the increase in knowledge about the birth process related to food selection during pregnancy, to the process of childbirth, as well as understanding of appropriate oxygen saturation to prevent maternal and infant deaths. This study used descriptive analytical method. The population of this study amounted to 610 pregnant women who were undergoing treatment at hospitals in Medan City, where the samples taken amounted to 63 pregnant women who were undergoing treatment at hospitals in Medan City. The results of the study proved that pregnant women who were hospitalized in Medan Kota District aged 36-45 years had literacy about the birth process, and had low awareness in improving nutrition, in addition to poor hospital service procedures that affected the high neonatal mortality rate of babies born from the birth process in the hospital.